Lavender Aromatherapy to Reduce Anxiety During Intrauterine Insemination: A Randomized Controlled Trial - Tiffanny Jones MD (SAGE Publishing, 2021)
Background Infertility is a global public health issue. Therapies such as intrauterine insemination (IUI) are effective but may be associated with considerable anxiety. Preliminary data suggest that decreasing this anxiety might lead to improved outcomes. Objective To determine whether lavender aromatherapy (LA) reduces anxiety during an IUI procedure. Methods A randomized controlled trial of women undergoing IUI at a hospital-based fertility clinic. The intervention and comparison were the use of LA vs water. Measurements were the change in anxiety level during an IUI procedure, with secondary assessment of pain scores, patient satisfaction, and pregnancy rates. Results In total, 67 women were screened, and 62 women randomly assigned to either placebo (n = 31) or LA (n = 31). No differences were observed in baseline demographic characteristics or visual analog scores for anxiety before IUI (mean [95% CI], 33.9 [25.2 to 45.6] mm vs 41.0 [33.0 to 49.0] mm) in the LA and placebo groups. However, a statistically significant change in anxiety was observed after LA inhalation during the procedure (mean [95% CI], −11.2 [−19.1 to −3.2]) compared with placebo (mean [95% CI], 1.3 [−5.6 to 8.2]; P = .02). No significant difference was observed in pain during IUI in the LA group vs placebo group. Patient satisfaction was high, with 93% of respondents in the LA group satisfied with the aromatherapy during their procedure. Additionally, 76% of participants who received placebo reported that they would prefer to use LA during their IUI. No statistically significant difference was detected in pregnancy rates between the 2 groups: 19.4% with LA vs 9.7% with placebo ( P = .47). Conclusion LA reduced anxiety and was preferred by women during IUI fertility treatments.